(Anti)estrogenic activity impacted by complex environmental matrices: A DOM and multiphase distribution approach. (January 2023) - Argolo, Allan dos Santos; Gomes, Giselle; Bila, Daniele Maia
Abstract: The presence of estrogenic endocrine disruptors in aquatic environments has been a concern and bioassays are recommended tools for their monitoring. However, the physicochemical properties of contaminants and the environmental matrix features may influence the resultant response. This study aimed to assess this influence on the Yeast Estrogen Screen (YES) assay. Mixtures of 17β-estradiol (E2) and humic acid (HA) were evaluated through the Schild approach aiming to investigate the interactions between estrogens and dissolved organic matter (DOM). Moreover, environmental samples from municipal landfill leachate and wastewater treatment plant (WWTP) influents and effluents were screened for (anti)estrogenic activity at both dissolved and particulate phases. Finally, results were statistically confronted with physicochemical parameters through principal component analysis (PCA). The HA test concentrations strongly reduced the E2 response, even at low levels. Humic substances may not only reduce estrogen bioavailability, but also interfere with the assay mechanism through enzymatic inhibition thus masking the sample estrogenic potential. Landfill leachate had total E2-Eq in the range 1282–2591 ng L −1, while WWTP influent and effluent were in the range 12.1–41.4 and <DL–2.3 ng L −1, so estrogenicity was reduced 92% in average. Particulate phase was responsible for 33–100% of measured E2-Eq between matrices, though cytotoxicity occurred in some extracts. Antiestrogenic activity was observed in both phases and might also have masked the estrogenicity of samples. PCA did not resulted in positive correlations supporting a multiphase distribution pattern of estrogenic compounds. Nevertheless, the solids and organic matter characteristics supported the data interpretation. In conclusion, the in vitro YES assay is subjected to factors intrinsic to the environmental sample that can influence on the measured estrogenic response. Therefore, results interpretation should be performed together with organic matter characterization parameters, cytotoxicity and antiestrogenic activity evaluation. Graphical abstract: Image 1 Highlights: Humic acid induces strong antagonistic effect in the Yeast Estrogen Screen. Landfill leachate, WWTP influents and effluents were highly estrogenic. Cytotoxicity was recurrently associated with particles >0.7 μm. DOM, antiestrogenic activity and phase distribution influenced on estrogenic response.